2022
DOI: 10.1186/s12937-022-00764-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a probiotic-containing infant formula supplemented with 2’-fucosyllactose: a double-blind randomized controlled trial

Abstract: Background Human milk oligosaccharides (HMOs) have important and diverse biological functions in early life. This study tested the safety and efficacy of a starter infant formula containing Limosilactobacillus (L.) reuteri DSM 17938 and supplemented with 2’-fucosyllactose (2’FL). Methods Healthy infants < 14 days old (n = 289) were randomly assigned to a bovine milk-based formula containing L. reuteri DSM 17938 at 1 × 107 CFU/g (control group; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…A formula including 2′-FL and LNnT showed softer stool consistency in another investigation 118 . Stool consistency in infants fed 2′-FL and FOS-containing formula was found to be comparable to that of breast-fed infants 157 , 158 .…”
Section: Hmos and Anthropometrymentioning
confidence: 73%
See 1 more Smart Citation
“…A formula including 2′-FL and LNnT showed softer stool consistency in another investigation 118 . Stool consistency in infants fed 2′-FL and FOS-containing formula was found to be comparable to that of breast-fed infants 157 , 158 .…”
Section: Hmos and Anthropometrymentioning
confidence: 73%
“…Infant formula supplemented with 2′FL alone, 2′FL combined with LNnT, and a blend of five HMOs (2′-FL, 3-FL, LNT, 3′-SL, 6′-SL) in formula with intact and hydrolyzed protein have all been shown to be well tolerated in clinical trials 118 , 149 , 150 , 153 , 155–157 . Stool consistency, flatulence, and the frequency of spitting up/vomiting were similar in infants given formula containing with or without HMOs 149 , 157 , 158 . In an RCT testing, a mix of 5 HMOs in infant formula, the stools in the HMO supplemented formula group were more soft, frequent, and yellow.…”
Section: Hmos and Anthropometrymentioning
confidence: 91%
“…4 The safety evaluation and clinical trials of 2′-FL have widely been studied, and it is suggested that 2′-FLcontaining infant formula is safe and well-tolerant for infants. 5 2′-FL has been approved as Generally Recognized As Safe (GRAS) by American Food and Drug Administration (FDA) and commercially added to infant formula. These confirmed health benefits and promising applications have driven the extensive researches of 2′-FL, particularly in the field of biosynthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The health benefits of 2′-FL have been thoroughly investigated and confirmed, especially for infants, including prebiotic effect, immune modulators, and maintaining barrier function of gut epithelial cells . The safety evaluation and clinical trials of 2′-FL have widely been studied, and it is suggested that 2′-FL-containing infant formula is safe and well-tolerant for infants . 2′-FL has been approved as Generally Recognized As Safe (GRAS) by American Food and Drug Administration (FDA) and commercially added to infant formula.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the better adherence of FN041 (unpublished data). The addition of DSM17938 to neonatal formula promoted growth in children and was well-tolerated ( 48 , 49 ), implying that FN041 could be used in the maternal formula and infant formula during the late trimester and lactation for the prevention of neonatal AD.…”
Section: Discussionmentioning
confidence: 99%